SIRT3 Deficiency Promotes High‐Fat Diet‐Induced Nonalcoholic Fatty Liver Disease in Correlation with Impaired Intestinal Permeability through Gut Microbial Dysbiosis. Issue 4 (27th December 2018) - Chen, Mengting; Hui, Suocheng; Lang, Hedong; Zhou, Min; Zhang, Yong; Kang, Chao; Zeng, Xianglong; Zhang, Qianyong; Yi, Long; Mi, Mantian
Abstract : Scope: Sirtuin 3 (SIRT3) plays a protective role against nonalcoholic fatty liver disease (NAFLD) by improving hepatic mitochondrial dysfunction. Gut microbiota imbalance contributes to the pathogenesis of NAFLD, yet the underlying mechanism linking SIRT3 with gut microbiota in NAFLD progression remains obscure. Methods and results: Wild‐type 129 mice and SIRT3 knockout (SIRT3KO) mice are placed under a chow diet or high‐fat diet (HFD) treatment for 18 weeks. HFD resulted in a significantly increased hepatic steatosis and inflammation, which are exacerbated in SIRT3KO mice. The gut microbiota by 16s rRNA gene sequencing and phylogenetic reconstruction of unobserved states analysis are characterized. Lack of SIRT3 facilitates gut microbial dysbiosis in mice following HFD, with increased Desulfovibrio, Oscillibacter, and decreased Alloprevotella . SIRT3 deficiency resulted in an impaired intestinal permeability and inflammation in HFD‐fed mice, which can be attenuated by sodium butyrate (NaB). SIRT3KO HFD‐fed mice is followed by an increased lipopolysaccharide into the circulation and dysregulated expressions of cannabinoid receptor 1 and 2 in colon and liver, which are significantly associated with the alterations of intestinal microbiota. Conclusions: SIRT3 deficiency promotes NAFLD progression in correlation with impaired intestinal permeability through gut microbiota dysbiosis. Abstract : SIRT3, an integral regulator of mitochondrial function, is essential for maintaining gut homeostasis, which maintains butyrate production and prevents translocation of lipopolysaccharide through the intestinal barrier. Also, SIRT3 deficiency exaggerates high‐fat‐diet‐induced hepatic steatosis and inflammation through dysregulated expressions of cannabinoid receptor 1 in colon and liver, which are significantly associated with the altered intestinal microbiota.